Solution for a conservative nonlinear singular oscillator in plasma physics using harmonic balance method - Hosen, Md. Alal; Chowdhury, Md. Sazzad Hossien; Akbar, M. Ali (Kaerntner Botanikzentrum, Klagenfurt, Austria, 2015)
In this article, an analytical technique has been developed to determine approximate solutions of nonlinear singular oscillator. Usually, a set of nonlinear algebraic equations is solved in analytical approximate method. However, analytical solutions of these algebraic equations are not always possible, especially in the case of a large oscillation. In this article, different small parameters of the same nonlinear problems are found, for which the parameter based power series solution to these nonlinear algebraic equations give the desired results even for the large oscillation. The method is illustrated by singular oscillator, but it is also useful for many other nonlinear problems.